Artemisinins as Anticancer Drugs: Novel Therapeutic Approaches, Molecular Mechanisms, and Clinical Trials - Xu, Cangcang; Zhang, Huihui; Mu, Lingli; Yang, Xiaoping (Frontiers in Pharmacology, 2020)
Artemisinin and its derivatives have shown broad-spectrum antitumor activities in vitro and in vivo. Furthermore, outcomes from a limited number of clinical trials provide encouraging evidence for their excellent antitumor activities. However, some problems such as poor solubility, toxicity and controversial mechanisms of action hamper their use as effective antitumor agents in the clinic. In order to accelerate the use of ARTs in the clinic, researchers have recently developed novel therapeutic approaches including developing novel derivatives, manufacturing novel nano-formulations and combinating ARTs with other drugs for cancer therapy. The related mechanisms of action were explored. This review describes ARTs used to induce non-apoptotic cell death containing oncosis, autophagy, and ferroptosis. Moreover, it highlights the ARTs-caused effects on cancer metabolism, immunosuppression and cancer stem cells and discusses clinical trials of ARTs used to treat cancer. The review provides additional insight into the molecular mechanism of action of ARTs and their considerable clinical potential.